Immunotherapy or targeted therapy: What will be the future treatment for anaplastic thyroid carcinoma? - Gao, Xiaoni; Hong, Chengcheng; Xie, Yang; Zeng, Xiangtai (Frontiers in Oncology, 2023)
Anaplastic thyroid carcinoma (ATC) is a rare and aggressive form of thyroid carcinoma (TC). Currently, there are no effective treatments for this condition. In the past few years, targeted therapy and immunotherapy have made significant progress in ATC treatment. Several common genetic mutations have been found in ATC cells, involving different molecular pathways related to tumor progression, and new therapies that act on these molecular pathways have been studied to improve the quality of life of these patients. In 2018, the FDA approved dabrafenib combined with trametinib to treat BRAF-positive ATC, confirming its therapeutic potential. At the same time, the recent emergence of immunotherapy has also attracted wide attention from researchers. While immunotherapy for ATC is still in the experimental stage, numerous studies have shown that immunotherapy is a potential therapy for ATC. In addition, it has also been found that the combination of immunotherapy and targeted therapy may enhance the anti-tumor effect of targeted therapy. In recent years, there has been some progress in the study of targeted therapy or immunotherapy combined with radiotherapy or chemotherapy, showing the prospect of combined therapy in ATC. In this review, we analyze the response mechanism and potential effects of targeted therapy, immunotherapy, and combination therapy in ATC treatment and explore the future of treatment for ATC.